DMT Method Approach for Liquefaction Hazard Vulnerability Mapping in Bantul Regency, Yogyakarta Province, Indonesia - Khori Sugianti; Anggun Mayang Sari; Arifan Jaya Syahbana (Geological Agency, 2015)
DOI:10.17014/ijog.2.1.53-61On May 27 2006, an earthquake (Mw 6.2) occurring in Bantul, Yogyakarta Special Province, triggered liquefaction phenomenon such as sand boiling and lateral spreading. Knowledge of the liquefied soil layers is required to mitigate the hazard. The purpose of this research is to determine the depth and thickness of liquefiable soil layers using the flat blade dilatometer test (DMT) method. The horizontal stress index values (KD) obtained from the DMT were used to calculate the cyclic resistance ratio (CRR), while the PGA (peak ground acceleration) calculated by the software EZ-FRISK 7.52 were employed to determine the cyclic stress ratio (CSR). The DMT-based liquefaction potential analysis shows that the thickness of liquefiable soil layers ranges from 1.8 to 4.0 m. These results show a good agreement with the previous analysis based on CPT (cone penetration test) data. The analysis also indicated that, for the given earthquake magnitude and PGA, the liquefiable soil layers are characterized by a range of maximum KD value from 2.1 to 3.7.